The Analysis of Teacher Talk and The Characteristic of Classroom Interaction in English for Young Learner - KHUSNAINI, NURUL (ELT Forum: Journal of English Language Teaching, 2019)
ABSTRACT This study was aimed to find out the type of teacher talk and the characteristic of classroom interaction take place in the English language classroom of Semarang Multinational School.This study applied descriptive qualitative research. There were two activities in gathering the data of this study: observation and audio recording. In analyzing this study, the researcher used interactive theory proposed by  Flander (1989). The findings showed that based on Flanders Interaction Analisys Categories (FIAV), the teacher indirectly influenced the students in teaching and learning process by relying hard on asking questions. Besides asking questions to students, teacher also used (1) accepting students? feeling, (2) praising or encouraging students, and (3) accepting or even using students? ideas. In addition the pattern of content cross interaction tended to be more on asking questions than lecturing behavior. It indicated that teacher often relied on asking questions to students in the teaching and learning process rather than to introduce new learning material and help conveying information to students. In conclusion, the teacher indirectly influenced the students in the teaching and learning process. This kind of interaction indicated that teacher often relied on asking rather than lecturing the students. Keywords: Teacher Talk, Classroom Interaction, Flanders Interaction Analysis Categories